Gastrointestinal Symptoms Profile in Pediatric Patients With Gastroparesis Compared to Healthy Controls. Issue 2 (1st June 2022) - Febo-Rodriguez, Liz; Chumpitazi, Bruno P.; Musaad, Salma; Sher, Andrew C.; Varni, James W.; Shulman, Robert J.
Abstract : Objectives: The primary objective was to compare the patient-reported gastrointestinal symptoms profiles of pediatric patients with gastroparesis to matched healthy controls using the Pediatric Quality of Life Inventory™ (PedsQL™) Gastrointestinal Symptoms Scales. The secondary objectives were to compare pediatric patients with gastroparesis to pediatric patients with gastroparesis-like symptoms and normal gastric emptying and to compare pediatric patients with gastroparesis-like symptoms and normal gastric emptying to matched healthy controls. Methods: The PedsQL™ Gastrointestinal Symptoms Scales were completed by 64 pediatric patients with gastroparesis, 59 pediatric patients with gastroparesis-like symptoms and normal gastric emptying, and 200 age, gender, and race/ethnicity matched healthy controls. The PedsQL™ Gastrointestinal Symptoms Scales encompass 10 individual multi-item scales which measure stomach pain, stomach discomfort when eating, food and drink limits, trouble swallowing, heartburn and reflux, nausea and vomiting, gas and bloating, constipation, blood in poop, and diarrhea/fecal incontinence. Based on gastric emptying scintigraphy testing, those with abnormal gastric retention were classified as having gastroparesis. Results: The gastrointestinal symptoms profile analysis identified large differences between those with gastroparesis compared to healthy controls (most P <0.001), with the largest effect sizes for upper gastrointestinal symptoms including stomach pain, stomach discomfort when eating, food and drink limits, nausea, and vomiting. Those with gastroparesis self-reported similar gastrointestinal symptoms to those with normal gastric emptying, except for increased constipation. Conclusions: Pediatric patients with gastroparesis self-reported broad multidimensional gastrointestinal symptoms profiles in comparison to healthy controls with large differences, indicating the critical need for more highly efficacious interventions to bring patient functioning within the normal range of healthy functioning.